Impaired IFN-γ-dependent STAT3 Activation Is Associated With Dysregulation of Regulatory and Inflammatory Signaling in Monocytes of Ulcerative Colitis Patients. Issue 6 (9th November 2020) - Cordes, Friederike; Lenker, Eva; Weinhage, Toni; Spille, Lea J; Bettenworth, Dominik; Varga, Georg; Schmidt, Hartmut H; Foell, Dirk
Abstract: Background: The Janus kinase/signal transducer and activator of transcription (JAK/STAT) inhibitor tofacitinib has been recently approved for the treatment of ulcerative colitis (UC) but not Crohn's disease (CD). Systematic analysis of the JAK/STAT pathway in inflammatory bowel disease is still missing. The aim of this study was to investigate JAK/STAT activation and adjacent signaling in monocytes of patients with inflammatory bowel diseases, which are key players in inflammatory responses. Methods: Blood samples of active UC (n = 28) and CD patients (n = 28) and healthy controls (n = 22) were collected for primary monocyte investigation. STAT phosphorylation (pSTAT), cytokine secretion, and surface marker expression ± prior tofacitinib blockade in addition to Th-17 and regulatory T cell induction in cocultures were analyzed upon interferon (IFN)-γ timulation. Results: Baseline frequencies of pSTAT1 + and pSTAT3 + monocytes were significantly higher in UC, whereas IFN-γ-associated crosstalk induction of pSTAT3 + monocytes was missing in UC-derived monocytes compared with controls and CD. This coincided with decreased interleukin (IL)-10 and cluster of differentiation (CD)39 levels, diminished regulatory T cell (Treg) induction, and increased IL-12 and IL-23 secretion compared with controls, which was not observed in CD monocytes. Tofacitinib induced stronger inhibition of inflammatory cytokine release (IL-6, TNFα, IL-12, IL-23) in UC compared with CD monocytes. Conclusions: In UC monocytes, IFN-γ-associated activation of the JAK/STAT pathway is impaired with an imbalance between STAT1 and STAT3, coinciding with stronger induction of inflammatory monocytes by IFN-γ compared with controls or CD. The fact that tofacitinib had stronger regulatory impact on UC than on CD monocytes further underlines a stronger inflammatory involvement of the JAK/STAT pathway in UC pathogenesis, which might result from missing STAT3 activation to counteract STAT1-induced inflammation.